(untitled) (CIPEEX, 2025)
This paper examines jurisdiction over latrocínio (robbery resulting in death), classifying it as an offence against property and therefore subject to bench trial, notwithstanding the lethal outcome; by contrast, intentional crimes against life fall within the constitutional remit of the Jury Court. It aims to define, drawing on Article 157 §3 of the Brazilian Criminal Code, the constitutional framework governing jury competence, and pertinent scholarship, the criteria that exclude the Jury Panel’s jurisdiction in robbery-with-homicide cases. Methodologically, it adopts a doctrinal-normative and descriptive approach, clarifying the protected legal interest and the ensuing procedural consequence. The findings indicate that the typification of latrocínio as a property crime—rather than an intentional crime against life—triggers the jurisdiction of the bench judge, whereas the immediate protection of life in intentional homicide offences justifies Jury Court competence. It concludes that, although death occurs, latrocínio does not shift jurisdiction to the Jury Court; proceedings and judgment must occur before a single judge, consistent with the statutory nature of the offence and the proper constitutional allocation of jurisdiction.